Mac Solutions in Directional Communication Enabled Manets: A Brief Overview - Sadanand R. Inamdar; Jayashree I. Kallibaddi; B. Sathishbabu; Ravi M. Yadahalli (Research Highlights in Science and Technology Vol. 1, 2023)
5G’s network improvements have a far-reaching impact on the way people work, play and live around the world. Several applications of ad hoc networks like emergency relief activities in battlefield and disaster management, traffic management, border surveillance, smart precision farming that are based on new 5G standards demand for higher network throughput, lower latency. Technically, increasing the upper limit of network throughput in such applications is possible when protocols have improved antenna technologies that exploit the characteristics of directional antennas. Several recently proposed Directional Media Access Control (DMAC) protocols for ad hoc networks advocate the use of directional antenna over the traditional Omni-directional antenna for 10 to 100 times improvement over the current 4G LTE technology with a speed of up to 10 Gbps, which exploits benefits of Spatial Division Multiple Access. Researchers have shown how to design DMAC protocols using directional random-access scheme for effective channel utilization which eliminatesthe challenges of beam-forming nature of the antenna. The design goal of DMAC protocols is to efficiently arbitrate channel access and decrease the total number of packet collisions during data transmission and to achieve efficient medium utilization.This paper reviews the recently proposed medium access protocols to investigate medium access strategy being used to address the directional hidden terminal problem and deafness problem. The study of the methods adopted and underlying key ideas of the medium access protocols help researchers to understand, design and reveal the progress made in developing effective channel access protocols for directional communication enabled ad hoc networks which will meet the demands of future ultra-high bandwidth and high data rate communication.